Inflated inequality or unequal inflation? A case for sustained 'two-sided' austerity in Greece - Vlassis Missos; Peter Blunt; Charalampos Domenikos; Nikolaos Pontis (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2024)
Empirical data are presented on expenditure inequality dynamics in Greece, how they evolved during a period of deep socio-economic crisis, and how they were sustained by inflation. A differentiated approach to expenditure inequalities is applied that reveals the size of contraction of total private expenditure and its sub-categories for different expenditure groups of the population. One of the most important aspects of expenditure inequality in Greece concerns the inability of the widely used measures of dispersion to capture the real adjustment magnitude that occurs during a period of overlapping crises. A close examination of private expenditure enables the distributional effects of contractionary measures in Greece, which are intensified by inflation, to be portrayed as inverted austerity. It is argued that the 2021-2022 inflationary pressures in Greece were a continuation of the policies used to advance the purposes of internal devaluation that had been in effect since at least 2010. The data show that the poor in Greece have suffered unprecedented hardship, and that inequality has risen sharply.
Keywords: D30; D63; E21; E31; 330; Inequality; Household budgets; Inflation; Austerity